The Effect of Game – like Exercises on Tactical Thinking, and the Accuracy of Forward and Backward Fast Setting in Volleyball Setters Aged 15 – 18 Years Old - NEAMAH, khalid; Sabhan , Hussein (Journal of Physical Education, 2022)
The research aimed at designing game like exercises to develop tactical thinking the accuracy of performing forward and backward setting in volleyball setters aged 15 – 18 years old as well as identifying the effect of these game-like exercises on tactical thinking the accuracy of performing forward and backward setting in volleyball setters aged 15 – 18 years old. The researchers used the experimental program on (62) volleyball setters aged 15 – 18 years old from Al Senaa, Al Shorta, Al Jaesh, and the national center for gifted in volleyball, ministry of youth and sport. The subjects were (10) setters divided equally into two groups; controlling and experimental groups. The data was collected and treated using SPSS to conclude that game like exercises significantly developed tactical thinking and fast setting accuracy in volleyball setters aged 15 -18 years old.